Keserasian Alat Gali Muat Excavator Komatsu PC 500LC-10R dan Alat Angkut Dump Truck STD Scania P410B6X4 XT Pada Pengupasan Lapisan Tanah Penutup PT. Satria Alam Manunggal Site TOPB Desa Buhut Jaya Provinsi Kalimantan Tengah - Lutfiana, Alifah; Usup, Hepryandi L. Djanas; Murati, Ferra; Fridtriyanda, Asri; Andri, Yusias (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
PT. Satria Alam Manunggal is a company specializing in mining, specifically as a mining contractor for PT. Telen Orbit Prima (TOP). One of its activities is the removal of overburden. The purpose of this study is to analyze the match factor of loading and hauling equipment in the removal of overburden. Using quantitative and descriptive methods, the researchers examined issues related to the match factor in overburden stripping activities at the PT. Satria Alam Manunggal TOPB site. From the observations, the cycle time of the loading equipment in fleet 1 was 26.40 seconds or 0.44 minutes, while in fleet 2 it was 27.75 seconds or 0.46 minutes. The cycle time of the transport equipment in fleet 1 was 833.1 seconds or 13.89 minutes, while in fleet 2 it was 930 seconds or 15. 50 minutes. From the cycle time of the loading and transport equipment in both fleets, the compatibility value in fleet 1 was 1.14 and in fleet 2 was 1.07. The factors that hindered the compatibility of the loading and transport equipment were the excavator waiting for the dump truck to maneuver, the difference in speed between dump trucks, and the loading time being too long